2016
DOI: 10.3399/bjgp16x683989
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of adult chronic and acute leukaemia before diagnosis: large primary care case-control studies using electronic records

Abstract: BackgroundLeukaemia is the eleventh commonest UK cancer. The four main subtypes have different clinical profiles, particularly between chronic and acute types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Datalink (CPRD), mirroring the authors' previous cancer studies. [16][17][18][19][20][21][22][23] The CPRD contains anonymised medical records of patients from participating practices across the UK, representing roughly 8.8% of the population. Information is stored for clinical events such as symptoms, investigations, prescriptions, and diagnoses, together with patient demographics.…”
Section: Resultsmentioning
confidence: 99%
“…Datalink (CPRD), mirroring the authors' previous cancer studies. [16][17][18][19][20][21][22][23] The CPRD contains anonymised medical records of patients from participating practices across the UK, representing roughly 8.8% of the population. Information is stored for clinical events such as symptoms, investigations, prescriptions, and diagnoses, together with patient demographics.…”
Section: Resultsmentioning
confidence: 99%
“…This study uses a robust data source, the CPRD, which has been used extensively in past studies of cancer risk markers. [11][12][13][14] The use of NCRS data is a further strength, identifying incident cases that may have been unrecorded in the CPRD. Blood counts are electronically transmitted to the CPRD, reducing the risk of recording error.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…15 Since then, English and Swedish case-control studies have reported that weight loss is associated with acute and chronic leukaemia and non-metastatic colorectal cancer. 35,36 For some cancer sites there have been no studies on the association with unexpected weight loss in primary care. Our analysis is the first to focus on the association between unexpected weight loss and cancer across all sites.…”
Section: Findings In Contextmentioning
confidence: 99%